276. Vancomycin Utilization in a Neonatal Intensive Care Unit. (26th November 2018) - Mongkolrattanothai, Kanokporn; Stach, Leslie; Orbach, Regina; Chin, Steven; Nair, Srikumar; Su, Hsiang-Fen
Abstract: Background: The collaboration between antimicrobial stewardship program (ASP) and NICU has implemented key strategies including antibiotic restriction, audits and direct feedback, education, standardized guidelines for neonatal sepsis, and discontinuation of vancomycin at 48 hours if cultures are negative for resistant Gram-positive cocci (GPC). We aimed to evaluate the use of vancomycin in our NICU after implementing key changes in 2016, and determine further areas of improvement. Methods: Retrospective chart review was conducted in NICU patients who received vancomycin between January 1, 2017 and December 31, 2017. The use of vancomycin for surgical prophylaxis was excluded. The outcome measures were the use of vancomycin according to the guidelines and its deviations, monitoring of drug levels, renal function, microbiological, and clinical outcomes. Utilization of vancomycin was also evaluated by days of therapy (DOT) per 1, 000 patient-days. Results: There were 336 vancomycin courses administered to 176 infants. Most of vancomycin use (252/336, 75%) was discontinued at 48 hours. Of these, no infants developed invasive Gram-positive infections requiring reinitiating of vancomycin. Among those with continued vancomycin courses, more than half (45/84, 54%) occurred in the absence of evidence of resistant GPC infections. Commonly stated reason for continuation of vancomycin was the infants' severity of illness. Of the total 319 troughs drawn, 24 (7.5%) had subtherapeutic (<5) trough whereas 61 (19%) had supratherapeutic (>15). Acute kidney injury (increase in serum Cr ≥ 1 time baseline) was found in 6 courses (1.8%), in which four courses (67%) received vancomycin for 48 hours or less. Vancomycin utilization in year 2017 was 61.5 per 1, 000 patients/day which has decreased compared with those of previous years 2015–2016 (71.7 and 72.3, respectively). Conclusion: The majority of vancomycin use was consistent with our existing guidelines. However, most of our use was for 48 hours, questioning the value of empirical vancomycin for suspected sepsis in our NICU. More judicious use of vancomycin could be improved if subsets of high-risk patients could be identified for initiation of empirical vancomycin. Disclosures: All authors: No reported disclosures.